2015
DOI: 10.1074/jbc.l115.641175
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Sabatelli et al.: Detecting Collagen VI in Bethlem Myopathy

Abstract: This is a response to a letter by Sabatelli et al. (1).In their letter, Sabatelli et al. (1) refer to our recent paper on a Bethlem myopathy patient with a homozygous COL6A2 p.D871N mutation. The authors are concerned that our data are inconsistent because we reported that collagen VI staining was absent in muscle when using monoclonal antibody VI-26 but present in very reduced amounts in cultured fibroblast extracellular matrix when detected with monoclonal antibody 3C4 (2). We agree that based on our in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…There has been discussion in the collagen VI literature regarding the use of VI-26/MAB3303 and 3C4 for immunostaining patient muscle tissue and fibroblasts [ 15 , 16 ]. It has been reported that VI-26 is less sensitive at detecting collagen VI in muscle and fibroblast preparations compared to 3C4 leading to an underestimation of the amount of collagen VI degradation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been discussion in the collagen VI literature regarding the use of VI-26/MAB3303 and 3C4 for immunostaining patient muscle tissue and fibroblasts [ 15 , 16 ]. It has been reported that VI-26 is less sensitive at detecting collagen VI in muscle and fibroblast preparations compared to 3C4 leading to an underestimation of the amount of collagen VI degradation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly-used antibodies include VI-26 (MAB3303) raised against tissue-purified collagen VI, 3C4/Mab1944 for the α3 chain, and 6A1-H200 for α1. Public discussion within the collagen VI community about the use of antibodies for the molecular and histological analysis of collagen VI mutations [ 15 , 16 ] stimulated an effort to authenticate commonly-used antibodies. In this report we define chain specificity and relative sensitivities of 23 commercially-available collagen VI antibodies by immunohistochemistry and immunoblotting.…”
Section: Introductionmentioning
confidence: 99%